Comparing gradient boosting machine and Bayesian threshold BLUP for genome‐based prediction of categorical traits in wheat breeding - Osval Antonio Montesinos‐López; Henry Nicole Gonzalez; Abelardo Montesinos‐López; María Daza‐Torres; Morten Lillemo; José Cricelio Montesinos‐López; José Crossa (The Plant Genome, 2022)
Abstract Genomic selection (GS) is a predictive methodology that is changing plant breeding. Genomic selection trains a statistical machine‐learning model using available phenotypic and genotypic data with which predictions are performed for individuals that were only genotyped. For this reason, some statistical machine‐learning methods are being implemented in GS, but in order to improve the selection of new genotypes early in the prediction process, the exploration of new statistical machine‐learning algorithms must continue. In this paper, we performed a benchmarking study between the Bayesian threshold genomic best linear unbiased predictor model (TGBLUP; popular in GS) and the gradient boosting machine (GBM). This comparison was done using four real wheat (Triticum aestivum L.) data sets with categorical traits measured in terms of two metrics: the proportion of cases correctly classified (PCCC) and the Kappa coefficient in the testing set. Under 10 random partitions with four different sizes of testing proportions (20, 40, 60, and 80%), we compared the two algorithms and found that in three of the four data sets, the GBM outperformed the TGBLUP model in terms of both metrics (PCCC and Kappa coefficient). In the larger data sets (Data Sets 3 and 4), the gain in terms of prediction accuracy of the GBM was considerably significant. For this reason, we encourage more research using the GBM in GS to evaluate its virtues in terms of prediction performance in the context of GS.